Hydrogen-rich syngas production from palm kernel shells (PKS) biomass on a downdraft allothermal gasifier using steam as a gasifying agent. (1st October 2021) - Barco-Burgos, J.; Carles-Bruno, J.; Eicker, U.; Saldana-Robles, A.L.; Alcántar-Camarena, V.
Highlights: Palm kernel shells were gasified in a downdraft allothermal gasifier using steam. Low temperatures favor CO production, and high temperatures the production of H2 . The volume fraction of H2 +CO reaches 80.4% and the cold gas efficiency of 80%. Abstract: The present study investigates the steam gasification of palm kernel shells (PKS) for hydrogen-rich N2 -free syngas production in a pilot-scale atmospheric downdraft allothermal gasifier. The feedstock material characterization, description of the gasifier design, auxiliary systems, operating conditions, and evaluation of the operating methodology for obtaining fuel gas are presented. The gasification equipment was tested under gasification temperatures between 800 and 950 °C and steam-biomass mass ratios between 0.2 and 1.2. The maximum H2 generation is achieved with a gasification temperature of 850 °C, steam/biomass ratio of 0.85, particle sizes of 2–3 mm, and biomass feed of 57.1 kg/h. The volume fraction of H2 + CO can reach 80.4%, and maximum cold gas efficiency of 80% with an average lower calorific value of 11.5 MJ/Nm 3